Effect of different planting times on the quantitative variation of total seed isoflavone content and composition in Korean soybean cultivars (Glycine max (L.) Merr.) - Kim, Hong-Sik; Kang, Beom-Kyu; Seo, Jeong-Hyun; Kim, Hyun-Tae; Ha, Tae-Joung; Oh, Jae-Hyeon; Shin, Sang-Ouk; Baek, In-Yeol (Journal of Crop Science and Biotechnology, 2021)
There is great interest in the enhancement of isoflavones as one of the functional ingredients in soybean. This study aimed to investigate the effects of changes in the ecological environment over different planting times on isoflavone content. A total of 28 Korean soybean cultivars were grown at different planting times in late May, mid-June, and early July and their isoflavone content was measured over 2 years (2017 and 2018). Analyses of variance revealed significant effects of genotypes, planting times, years, and their interactions on isoflavone content. The average content of total isoflavone, as well as its component groups of malonylglucoside and aglycon, increased significantly as the seed planting time was delayed from late May to early July. The accumulation of each isoflavone component varied with changes in the planting time. The isoflavone content of the soybean cultivars for soy-sprout and soy-paste and tofu were higher for plantings in early July than for those in late May and/or mid-June, except for the black soybean cultivars. Despite significant correlations of the isoflavone content of the 28 cultivars among the three planting times, the responses of individual cultivars varied in isoflavone content by planting time. When planting was delayed, the time to flowering and maturity was also delayed and the number of days of growth from planting or flowering to maturity decreased; however, this was not related to isoflavone content. When planting was delayed, the temperature during the ripening period from flowering to maturity was lower, which was inversely related to the isoflavone content.